Metode Studi Kasus Robert K. Yin dalam Penelitian Arsitektur - Hamdi Asysyauki, Akhmad; Rianto Widjaja, Robert (Sci-tech Journal, 2026)
A case study is a research method used to investigate complex and contextual phenomena in real-life settings. Case studies aim to understand a specific case in depth and comprehensively by considering various influencing factors. The method used in this research is a literature review or reference study to gain knowledge about the case study method formulated by Robert K. Yin. The purpose of this research is to analyze the case study research method formulated by Robert K. Yin in architectural research. Robert K. Yin's case study method can be widely used in research in the social sciences and other fields. The main characteristics of this case study are its focus on a single or multiple cases studied in real life, its ability to explain causal relationships by developing theory in the research design phase that relies on sources of evidence, and its ability to produce theoretical generalizations. In architectural research, Robert K. Yin's case study method can be applied, albeit partially, and can be combined with other methods.